Development of an Envelope Remodeling Decision Support Program considering Energy Performance for Apartment Buildings - Lee, Jun Ho; Jung, Hae Jun; Jeon, You Chang; Kim, Sung Wook; Kim, Sun Sook (Journal of the Architectural Institute of Korea, 2023)
As the number of old apartment buildings increase, the need and demand for remodeling is increasing. To improve the aesthetic features and energy performance of buildings, it is necessary to provide various alternatives for facade design and envelope specification at the early design stage. Iterative evaluation of energy performance and generation of design alternatives require a lot of time and manpower. Therefore, there is a need for an envelope remodeling assistant program to create efficient remodeling alternatives and evaluate their energy performance. The purpose of this study is to develop an assistant program to create alternatives of apartment building facade based on four design algorithms and to evaluate energy performance simultaneously. In addition, the applicability of the program was evaluated by comparing the developed program with ECO2-OD.
Keywords: Algorithm; Apartment building; Decision support; Energy performance; Envelope design; Remodeling